To err again is human: exploring a bidirectional relationship between pressure and performance failure feedback - Harris, D. J.; Vine, S. J.; Eysenck, M. W.; Wilson, M. R.- (Anxiety, Stress and Coping, 2019)
Background and Objectives: While the potentially negative effects of pressure on skilled performance have been well studied in laboratory-based research, theoretically driven questions based on real-world performance data are lacking.